(untitled) - Glendinning, Eric H (Oxford, 1993)
This book is used for student of Electronics in Universities, colleges and technical school. The book consists of 30 units containing authentic reading and passages from a wide variety of sources and covering a large range of topics from simple components to digital electronics. The book also contains a comprehensive glossary of important technical term in form of a mini-dictionary
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Sách giáo khoa dành cho người nước ngoài